Factors associated with early reperfusion improvement after intra-arterial fibrinolytics as rescue for mechanical thrombectomy. Issue 1 (2nd June 2021) - Kaesmacher, Johannes; Peschi, Giovanni; Abdullayev, Nuran; Maamari, Basel; Dobrocky, Tomas; Vynckier, Jan; Piechowiak, Eike; Pop, Raoul; Behme, Daniel; Sporns, Peter B; Styczen, Hanna; Virtanen, Pekka; et al.
Objective: To identify factors associated with early angiographic reperfusion improvement (EARI) following intra-arterial fibrinolytics (IAF) after failed or incomplete mechanical thrombectomy (MT). Methods: A subset of patients treated with MT and IAF rescue after incomplete reperfusion included in the INFINITY (INtra-arterial FIbriNolytics In ThrombectomY) multicenter observational registry was analyzed. Multivariable logistic regression was used to identify factors associated with EARI. Heterogeneity of the clinical effect of EARI on functional independence (defined as modified Rankin Score ≤2) was tested with interaction terms. Results: A total of 228 patients (median age: 72 years, 44.1% female) received IAF as rescue for failed or incomplete MT and had a post-fibrinolytic angiographic control run available (50.9% EARI). A cardioembolic stroke origin (adjusted odds ratio (aOR) 3.72, 95% confidence interval (CI) 1.39–10.0) and shorter groin puncture to IAF intervals (aOR 0.82, 95% CI 0.71–0.95 per 15-min delay) were associated with EARI, while pre-interventional thrombolysis showed no association (aOR 1.15, 95% CI 0.59–2.26). The clinical benefit of EARI after IAF seemed more pronounced in patients without or only minor early ischemic changes (Alberta Stroke Program Early Computed Tomography Score (ASPECTS) ≥9, aOR 4.00, 95% CI 1.37–11.61) and was absent in patients with moderate to severe ischemic changes (ASPECTS ≤8, aOR 0.94, 95% CI 0.27–3.27, p for interaction: 0.095). Conclusion: Early rescue and a cardioembolic stroke origin were associated with more frequent EARI after IAF. The clinical effect of EARI seemed reduced in patients with already established infarcts. If confirmed, these findings can help to inform patient selection and inclusion criteria for randomized-controlled trials evaluating IAF as rescue after MT.